Faktor - Faktor Yang Mempengaruhi Pendapatan Tenaga Kerja Perempuan Di Sektor Informal (Studi Kasus Pedagang Pasar Sanggeng Manokwari) - Framintolia Kaiway; Siti Aisah Bauw; Marcus R. Maspaitella (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2020)
Women act as wives and even mothers for children in the household by carrying out domestic tasks at home to take care of and serve their husbands and family members. When women have many dependent needs in the family, women take on a dual role to be absorbed in the world of work in the informal sector as traders by trading in the market in order to generate income in order to meet the needs of family life. This study aims to analyze the factors of age, working hours, education level, and the number of dependents on the income of female traders in Sanggeng Manokwari Market by using multiple linear regression analysis tools. The regression results show that there is a significant effect of age and working hours on the income of female traders, while the level of education and number of dependents does not show a significant effect on the income of female traders in the Sanggeng Manokwari Market.